Gênese e descaminhos do Ginásio Profissional Cristo Rei (1944-1956) de Uberlândia-MG - Oliveira, Sandra Ferreira de (2009)
The object of this thesis lies in the research on the history of education, specifically in the field of history of educational institutions. This research sought to examine the context and the events which have brought up a Catholic institution, the Christ the King Professional Gym, located in Uberlândia, MG. The school was initially maintained by the Congregation of Preciossísimo Blood and subsequently by the Salesian Congregation, under the Nonresidential male. The timeframes were marked from 1944, begin construction of the Gymnasium, and 1956, as this year, according to the documentation of this Gymnasium, completed the professional education of the institution. The aim is to rescue its history, its process of creation and installation, the routine institutional view of education offered by that entity. The Christ the King Gym, located in Uberlandia in 1944, had a significant contribution to the education of the population Uberlandense as it fell within the context of modernization that the city was experiencing. As the Hotel in question was declared as an institution of support to needy children, aimed to find traces that could confirm the characteristics of this school, through the assistance was the establishment of a social education of children. We used a variety of sources, from school to out of school, such as minutes of the final results, annual report, recognition, correspondence, photographs, interviews, local newspapers, local maps, census place codes of smaller, minutes of the Board Municipal de Uberlândia. Therefore, the research methodology of the aspects involved in the history of Christ the King Gym Training, the motion between the theoretical and the sources allowed the (re) construction of the historical period studied, and is evidence of what was intended. Accordingly, we chose to document analysis, and oral history as a research technique in order to elucidate more specific about the topic. It was found that the school resembled the other Catholic institutions, even to propose it as the primary objective, to remedy a lack of social Uberlândia - the problem of homeless children in an attempt to eliminate areas of public signs of disorder , translated by child poverty. Faced with the prospect of modernizing the city of Uberlandia, this school has won a prime space in the development process, but should be seen as one of the access roads to the progress of same. The emphasis on industrialization as a factor of modernity and progress represented a sort of urban space in this city. Would need to beautify it, give it a new structure, physical and intellectual, where the health, physical space and sanitation were necessary for this new city this sense, urban space was controlled by codes of posture, ducts and hierarchies, which are designed to neutralize the conflict, and promote the construction of a hygienic and orderly city. The Gym Training Christ the King presented a pedagogy that emphasized the educational concepts of the Christian man, based on assumptions and care in perspective confessional focused on training. Pursue a strategy of reconstruction of the individual in preparation for a profession and for their integration into the social environment. We can say that through this education, institutions reinforce the structures of existing classes, have different roles with respect to the formation of its clientele.